2022
DOI: 10.1108/jpbm-01-2022-3833
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a Disney masstige brand collaboration on perceptions of brand luxury: vertical versus horizontal product line extension strategies

Abstract: Purpose The purpose of this study is to examine the effects of a Disney collaboration and Disney product line extension type on the perceptions of masstige brands and purchase intentions. By identifying masstige brands as two types (i.e. born-masstige versus luxury-masstige brands), this study investigates how consumers respond to a Disney collection across different types of masstige brands. Design/methodology/approach The authors conducted three studies using an experimental approach. Findings Study 1 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…It has also been shown that many other factors may influence this relationship (e.g., Lee & Cho, 2023;Park et al, 2022;Singh, 2023).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that many other factors may influence this relationship (e.g., Lee & Cho, 2023;Park et al, 2022;Singh, 2023).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…It has also been shown that many other factors may influence this relationship (e.g., Lee & Cho, 2023; Park et al, 2022; Singh, 2023). These include not only the TBU image itself, which is an association with the average brand user image, but also its actual symbolic value to the consumer.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Masstige consumers also actively seek pleasurable experiences and engage in consumption as a means of indulgence, suggesting an emphasis on the hedonic value of luxury (Burhanudin, 2023;Das, Jebarajakirthy, & Sivapalan, 2022a;Ganguly et al, 2023;Goyal, 2020;Lee & Cho, 2023;Park et al, 2022;Purohit & Radia, 2022;Singh, 2023;Suzuki & Kanno, 2022). Additionally, several studies (Kumar et al, 2021;Nobre et al, 2023;Purohit et al, 2023) propose that masstige consumption leads to brand happiness.…”
Section: Masstige Buyersmentioning
confidence: 99%
“…Employing a quantitative research design, we developed a questionnaire rooted in previous research in the field (Das, Saha, & Roy, 2022d;Ho et al, 2023;Lee & Cho, 2023), making necessary (2020) and the hexagon and pyramid models developed by Paul (2015Paul ( , 2019. These models offer clear distinctions between the two categories, taking into account factors like target income (high/upper middle income vs. middle income), pricing (premium vs. moderate premium), and brand positioning (premium vs. upmarket).…”
Section: Research Setting and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation